Contribution of the Cointegration Theory to the Study of the Volatility of Financial Markets: Case of the Casablanca Stock Exchange (European Journal of Marketing and Economics, 2022)
The purpose of this paper is to highlight the long-term relationship between stock prices and dividends for a sample of companies listed on the Casablanca Stock Exchange between 2002 and 2016 using the cointegration theory especially its developments in panel data. Our results show that prices are more volatile than dividends, which rejects the possibility of their anticipation by the dividend discount model under the assumption of efficient markets.
Keywords: cointegration, prices, dividends, panel data, volatility